Is body mass index associated with outcomes of mechanically ventilated adult patients in intensive critical units? A systematic review and meta-analysis. - Yonghua Zhao; Zhiqiang Li; Tao Yang; Meiping Wang; Xiuming Xi (PLoS ONE)
Background Obesity paradox refers to lower mortality in subjects with higher body mass index (BMI), and has been documented under a variety of condition. However, whether obesity paradox exists in adults requiring mechanical ventilation in intensive critical units (ICU) remains controversial. Methods MEDLINE, EMBASE, China Biology Medicine disc (CBM) and CINAHL electronic databases were searched from the earliest available date to July 2017, using the following search terms: "body weight", "body mass index", "overweight" or "obesity" and "ventilator", "mechanically ventilated", "mechanical ventilation", without language restriction. Subjects were divided into the following categories based on BMI (kg/m2): underweight, < 18.5 kg/m2; normal, 18.5-24.9 kg/m2; overweight, BMI 25-29.9 kg/m2; obese, 30-39.9 kg/m2; and severely obese > 40 kg/m2. The primary outcome was mortality, and included ICU mortality, hospital mortality, short-term mortality (<6 months), and long-term mortality (6 months or beyond). Secondary outcomes included duration of mechanical ventilation, length of stay (LOS) in ICU and hospital. A random-effects model was used for data analyses. Risk of bias was assessed using the Newcastle-Ottawa quality assessment scale. Results A total of 15,729 articles were screened. The final analysis included 23 articles (199,421 subjects). In comparison to non-obese patients, obese patients had lower ICU mortality (odds ratio (OR) 0.88, 95% CI 0.0.84-0.92, I2 = 0%), hospital mortality (OR 0.83, 95% CI 0.74-0.93, I2 = 52%), short-term mortality (OR 0.81, 95% CI 0.74-0.88, I2 = 0%) as well as long-term mortality (OR 0.69, 95% CI 0.60-0.79, I2 = 0%). In comparison to subjects with normal BMI, obese patients had lower ICU mortality (OR 0.88, 95% CI 0.82-0.93, I2 = 5%). Hospital mortality was lower in severely obese and obese subjects (OR 0.71, 95% CI 0.53-0.94, I2 = 74%, and OR 0.80, 95% CI 0.73-0.89, I2 = 30%). Short-term mortality was lower in overweight and obese subjects (OR 0.82, 95% CI 0.75-0.90, I2 = 0%, and, OR 0.75, 95% CI 0.66-0.84, I2 = 8%, respectively). Long-term mortality was lower in severely obese, obese and overweight subjects (OR 0.39, 95% CI 0.18-0.83, and OR 0.63, 95% CI 0.46-0.86, I2 = 56%, and OR 0.66, 95% CI 0.57-0.77, I2 = 0%). All 4 mortality measures were higher in underweight subjects than in subjects with normal BMI. Obese subjects had significantly longer duration on mechanical ventilation than non-obese group (mean difference (MD) 0.48, 95% CI 0.16-0.80, I2 = 37%), In comparison to subjects with normal BMI, severely obese BMI had significantly longer time in mechanical ventilation (MD 1.10, 95% CI 0.38-1.83, I2 = 47%). Hospital LOS did not differ between obese and non-obese patients (MD 0.05, 95% CI -0.52 to 0.50, I2 = 80%). Obese patients had longer ICU LOS than non-obese patients (MD 0.38, 95% CI 0.17-0.59, I2 = 70%). Hospital LOS and ICU LOS did not differ significantly in subjects with different BMI status. Conclusions In ICU patients receiving mechanical ventilation, higher BMI is associated with lower mortality and longer duration on mechanical ventilation.